Psychometric properties of Turkish version of the interpersonal affect improvement strategies questionnaire (IAISQ) - AVCU, AKİF (My University, 2022)
The aim of this study was to adapt the Interpersonal Affect Improvement Strategies Questionnaire (IAISQ) into Turkish population, as well as to examine its validity and reliability estimates. The sample consisted of 610 university students. The original factor structure of the scale was confirmed in Turkish sample by confirmatory factor analysis (CFA). The internal reliability coefficient was found as .75 for overall scale (.74 for Positive Engagement subscale, .63 for Acceptance subscale). Significant correlation coefficients were found between the subscales of IAISQ and Interpersonal Emotion Regulation Questionnaire (IERQ), confirming a good criterion related validity. Overall results suggest that Turkish form of IAISQ is a valid and reliable measure to use for research purposes in order to investigate the Turkish students’ interpersonal affect improvement strategies.
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Social Sciences and Humanities; Education; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities